2020
DOI: 10.31234/osf.io/x6bpd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of a Self-Report Version of the German Strengths and Weaknesses of ADHD Symptoms and Normal Behavior Scale (SWAN-DE-SB)

Abstract: While the excellent psychometric quality of the German third-party report version of the Strengths and Weaknesses of ADHD Symptoms and Normal Behavior Scale (SWAN-DE) for school-aged children was recently demonstrated, a self-report version employable with adults was not available so far. The present study therefore aimed at developing and validating the SWAN-DE-SB, a self-report version of the SWAN-DE. Based on data obtained from 405 adults, 14 (3.5%) of them with a current ADHD diagnosis, normality, internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…In studies using confirmatory factor analysis ( 31 , 35 , 51 , 52 ), bifactor models were reported to have a better fit than non-hierarchical models; however, similar to studies with other measures, the results suggested a strong and reliable general ADHD factor but mostly weak or unreliable specific factors. A single study under peer review ( 38 ) reported similar results for the new self-report version of the SWAN. Blume et al.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In studies using confirmatory factor analysis ( 31 , 35 , 51 , 52 ), bifactor models were reported to have a better fit than non-hierarchical models; however, similar to studies with other measures, the results suggested a strong and reliable general ADHD factor but mostly weak or unreliable specific factors. A single study under peer review ( 38 ) reported similar results for the new self-report version of the SWAN. Blume et al.…”
Section: Introductionmentioning
confidence: 71%
“…Blume et al. ( 38 ) reported good internal reliabilities for the German version (α = 0.85 – 0.90). Up to now, only the parent and teacher versions of the SWAN have been validated in the Hungarian language showing good internal consistencies (α = 0.87 – 0.93) and convergent validity with the Hyperactivity subscale of the Strengths and Difficulties Questionnaire [SDQ ( 53 )] ( r = 0.67 - 0.74) ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses using these alternatives were scored as missing. Items were derived from the German self-report version of the Strength and Weaknesses of ADHD Symptoms and Normal Behaviour Scale (SWAN-DE-SB; Blume et al, 2023). Mean scores across all items were used as an indicator of students' self-regulation at the lesson level.…”
Section: Self-regulation At the Lesson Levelmentioning
confidence: 99%
“…Finally, self-regulation was measured using one item (i.e., "I am concentrating right now"), reflecting both the ability to direct attention to goal-relevant information and to inhibit responses to tempting or distracting stimuli. Scales assessing self-regulation as a trait similarly inquire about these abilities (e.g., Blume et al, 2020;Lidzba et al, 2013). Nevertheless, they additionally often also address children's motor activity, while also including items particularly dedicated to assess impulsiveness (e.g., "I can wait my turn").…”
Section: Limitations and Perspectivesmentioning
confidence: 99%